Understanding palliative care learning: A narrative inquiry exploring health care professionals' memorable experiences - Frances Kilbertus; Keely King; Susan Robinson; Sayra Cristancho; Sarah Burm (Elsevier, 2022)
Palliative care is an emotionally evocative domain of care, the complexities of which are not well understood. Palliative care has been described as a cultural shift in healthcare away from disease focused interventions toward a holistic and patient centered approach. Concerns have arisen around a lack of preparation for this approach to care following formal education programs across a variety of health professions. Demographics in many areas of the world demonstrate an increasing need for healthcare providers (HCPs) who are competent, confident, and engaged with this practice. Using narrative methodology to consider visual and verbal forms of storytelling, we explored memorable palliative care learning experiences of rural HCPs in Canada (2018-2019) to broaden understanding of how palliative care learning happens. HCPs across a variety of professions drew and recounted emotionally rich narratives that revealed personal and contextual dimensions as central to learning, inclusive of relationships, settings, and cultures. HCPs across professions recounted experiences that followed a common narrative arc that we call the 4Ds: difference, discomfort, disruptive, departure. This narrative arc is compatible with viewing learning as an ongoing process of transformation or becoming. Through considering the 4Ds and its implications for education, providers and educators can attune to opportunities to support students and colleagues as they emerge and grow as HCPs. Conversely, not attending to difficult, disruptive, and emotional aspects of learning may perpetuate hidden aspects of healthcare culture with possible negative impacts on provider experience and notions of professional identity.